TEACHING MEDIA DEVELOPMENT OF MATHEMATIC IN THE MATERIALS TRIGONOMETRY SUM AND TWO ANGLES DIFFERENCE BY USING GUI MATLAB - Cut Mulyawati; Salmawaty Salmawati; Muhammad Subianto; Reza Wafdan (Universitas Syiah Kuala, 2017)
Abstract. The aim of this research is to develop teaching media for mathematics specifically for materials on trigonometry using GUI Matlab. This media can be used as teaching and learning aid for students at senior high school, grade XI in the first semester. This learning media consists of instructions on how to use the media, learning materials, exercises and profile. The trigonometry materials which are discussed in this learning media consist of the sum and difference of two angles. The limitation on the angles that can be used are special angles in the interval -360o £ a,b £ 360o. The special angles are 0o, ±30o, ±45o, ±60o, ±90o, ±120o, ±135o, ±150o, ±180o, ±210o, ±225o, ±240o, ±270o, ±300o, ±315o, ±330o, and ±360o. The trigonometry functions such as sinus, cosine and as well as the operation addition (+) and subtraction (-) can be selected by hitting the appropriate button. Within each step, there is a check button and a next button to check the input true or false. If the value that entered incorrectly then the next step will not displayed and warning box will appear to report the location of error. Users have to fix the error in order to continue to the next step. Keywords: teaching learning media, trigonometry, GUI Matlab